2014
DOI: 10.2174/1874285801408010078
|View full text |Cite
|
Sign up to set email alerts
|

The Use of MALDI-TOF Mass Spectrometry, Ribotyping and Phenotypic Tests to Identify Lactic Acid Bacteria from Fermented Cereal Foods in Abidjan (Côte d’Ivoire)

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) protein analysis, automated ribotyping, and phenotypic tests (e.g., cell morphology, gas production from glucose, growth and acid production on homofermemtative-heterofermentative differential (HHD) agar medium, sugar fermentation patterns) were used to identify 23 lactic acid bacteria (LAB) isolated from fermented cereal foods available in Abidjan, Côte d’Ivoire. Pediococcus acidilactici (56.5%), Lactobacillus fermentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…plantarum and Lc. lactis has been shown in some works [14][15][16], but the identification at subspecies level should be assessed by the sequencing of protein-coding genes, which have a higher discriminating power than the 16S rRNA gene among closely related taxa. In the case of LAB, the pheS gene has been used, combined with MALDI-TOF MS, for their identification in some fermented foods [17,18], but, to date, these two techniques have not been used together to identify LAB in cheese samples.…”
Section: Introductionmentioning
confidence: 99%
“…plantarum and Lc. lactis has been shown in some works [14][15][16], but the identification at subspecies level should be assessed by the sequencing of protein-coding genes, which have a higher discriminating power than the 16S rRNA gene among closely related taxa. In the case of LAB, the pheS gene has been used, combined with MALDI-TOF MS, for their identification in some fermented foods [17,18], but, to date, these two techniques have not been used together to identify LAB in cheese samples.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, only phenotypic and genotypic methods were used to detect bacteria in bacteriological laboratories [ 66 ], and by the advancement of science, other techniques were used [ 67 ], such as MALDI-TOF MS, which is based on the study of bacterial proteins, which is an easy, fast, and accurate method that can replace other diagnostic procedures [ 68 ]. This method makes mass spectral for each microorganism unique as a fingerprint, identifying different bacterial genus and subspecies [ 34 ].…”
Section: Identification Of Bacteriamentioning
confidence: 99%
“…Lactobacillus salivarius was first isolated from children's saliva in Maryland, USA [1]. Later studies have shown that it exists in various habitats, including the oral cavity, the gastrointestinal tract, and in the vagina of animals (including humans), as well as food materials [2][3][4].…”
Section: Introductionmentioning
confidence: 99%